The geographic imagination of modernity : geography, literature, and philosophy in German Romanticism - Tang, Chenxi, 1968- (Stanford University Press, 2008)
Tang traces the emergence of the geographic paradigm in modern Western thought in the decades around 1800. This period represents an extraordinary intellectual threshold, a time when European society invented new conceptual strategies for making sense of itself. The book brings to light geography as one of the most important of these conceptual strategies. Its inquiry revolves, first of all, around the rise of geographic science, as it is in this science that the geographic imagination crystallizes. The second part offers a systematic study of the key spatial categories of the modern geographic imagination, including orientation, cultural landscape, and geohistory.